A note on the use of microbial insecticides for the control of tomato hornworms on flue-cured tobacco - Cheng, H.H.; Hanlon, J.J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1990)
Two formulations of Bacillus thuringiensis, Bactospeine-A and Thuricide-HPC, were applied on tobacco plants after topping to evaluate their effectiveness against tomato hornworm (Manduca quinquemaculata) in the laboratory and field. Both materials, regardless of the rates applied, gave complete control of the tomato hornworms. All the larvae fed slightly or moderately on the treated leaves during the first day after treatment, but thereafter, the larvae remained inactive on the treated leaves until death. There was little evidence of further feeding when the leaves were examined. The microbial insecticides had no detrimental effect on the beneficial insect parasite, Cotesia congragata, and no phytotoxicity was observed.